Heterogeneity in ordered choice models: A review with applications to self-assessed health - Greene, W.; Harris, Mark; Hollingsworth, B.; Weterings, T. (Centre for Research in Applied Economics, Curtin Business School, 2012)
Discrete variables that have an inherent sense of ordering across outcomes are commonly found in large datasets available to many economists, and are often the focus of research. However, assumptions underlying the standard Ordered Probit (which is usually used to analyse such variables) are not always justied by the data. This study provides a review of the ways in which the Ordered Probit might be extended to account for additional heterogeneity. Diering from other reviews in scope, application and relevance in economic settings, a series of issues pertaining to choices of variables, and the economic assumptions underlying each model are discussed in the context of measuring the underlying health of respondents. The models are applied to a wave of the Household, Income and Labour Dynamics in Australia survey, in order to check the appropriateness of such assumptions in an applied context.